Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai pada Kantor Kelurahan Bekasi Jaya - Nathasyah Nathasyah; Ari Sulistyowati; Bayu Seno Pitoyo; Tyna Yunita; Jumawan Jumawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The Effect of Work Motivation and Work Discipline on Employee Performance at the Bekasi Jaya Village Office. This study aims to find out whether there is an influence of work motivation and work discipline on employee performance at the Bekasi Jaya Village Office. In this study, the author uses a quantitative approach. This research was conducted using a saturated sampling approach. The number of the entire population used as a sample is as many as 41 respondents. Data collection technique by distributing questionnaires. The design used in this study uses IBM SPSS 26. The results of this study show that (1) work motivation has a positive and partially significant effect on employee performance of 4,110 > 1,685 with a significant value of 0.000 < 0.05 (2) work discipline has a positive and partially significant effect on employee performance of 2,708 > 1,685 with a significant value of 0.010 < 0.05 (3) work motivation and work discipline simultaneously or together have an effect on employee performance 61,872 > 3,245 with a significant value of 0.000 < 0.05. There are suggestions for future researchers to expand the sample size and include other variables such as leadership, work experience, and work environment to predict employee performance at the Bekasi Jaya Village Office. So that more information can be obtained about the factors that influence employee performance.